DUKUNGAN KELUARGA DALAM PERAWATAN SALAH SATU ANGGOTA KELUARGA DENGAN GANGGUAN JIWA DIWILAYAH KERJA PUSKESMAS WATULIMO KABUPATEN TRENGGALEK - Sulistyorini, Ariani; Laurentcia Gladis Harianto (STIKES dan AKZI Karya Husada Kediri, 2023)
Family support for patients with mental disorders is the attitude, actions, and acceptance of the family towards clients who experience mental disorders so that it can improve the client's recovery and compliance in undergoing therapy at home. The support provided is in the form of instrumental, assessment, informational, and emotional support. The research aims to determine family support in caring for a family member with mental disorders in the Watulimo Community Health Center work area. The research design used descriptive, the population and research sample were all families with one family member suffering from a mental disorder in the Watulimo Community Health Center Work Area, totaling 49 respondents, using the Total Sampling technique. The research was carried out on 20 March 2023 – 03 April 2023, the research variable was family support in the care of a family member with mental disorders, the research instrument used a questionnaire, and the data was analyzed using a percentage formula and interpreted quantitatively. The results of the research were 49 respondents, almost all respondents, namely 39 respondents (80%) had sufficient family support, a small portion of respondents, namely 5 respondents (10%) had good family support, and a small percentage of respondents, 5 respondents (10%) had insufficient family support. This is caused by factors such as gender, age, education, occupation, average income, and the type of mental disorder experienced by the family of the mentally ill. It is hoped that the results of the research will provide educational institutions with information about family support in caring for family members who suffer from mental disorders. Respondents can provide support by approaching mentally ill family members by providing attention and affection so that the support provided can be maximized. Health workers make regular visits to the homes of people with mental disorders to find out the client's condition.